Renovatio - Bolaños, José Carlo (Universidad de Costa Rica, 2015)
Renovatio consists in a group of spaces that work as a system to reactivate the life in the city ́s public space and landscape. The development of art and entertainment performances form part of its principal program activities. All these amenities in coalition with the citizen ́s appropriation of the space, shape the objectives of the project.